2005
DOI: 10.1080/00365540510037821
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate third-generation hepatitis C recombinant immunoblot assay and HCV RNA analysis: Isolated reactivity against NS5 associated with HCV viraemia in clinical patients but not blood donors

Abstract: It has previously been reported that singular reactivity against NS5 in the third generation hepatitis C virus (HCV) confirmatory recombinant immunoblot assay (RIBA-3) is not associated with detectable HCV RNA in sera. In order to investigate the significance of indeterminate HCV RIBA-3 results with particular regard to NS5, 165 sera with indeterminate RIBA-3 results were analysed for the presence of HCV RNA. Sera from blood donors constituted 58 of the 165 samples, whereas 11 were from immunocompromized patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…In addition, eleven samples presented antibodies that bound to antigen c33, while three samples had antibodies that bound to c22. HCV-RNA was not detectable in any of these samples, which is consistent with results that have been previously reported 8,11,15,16 . Nonetheless, in other studies 17 , the virus was successfully detected in some indeterminate RIBA samples.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, eleven samples presented antibodies that bound to antigen c33, while three samples had antibodies that bound to c22. HCV-RNA was not detectable in any of these samples, which is consistent with results that have been previously reported 8,11,15,16 . Nonetheless, in other studies 17 , the virus was successfully detected in some indeterminate RIBA samples.…”
Section: Discussionsupporting
confidence: 81%
“…However, other studies have indicated that RIBA‐indeterminate results may be associated with detectable HCV RNA. In a previous study [Cavazza and Lagging, 2005], 18% (19/107) were HCV RNA positive among 107 samples that were RIBA‐indeterminate, where only four (13.8%) HCV RNA positive samples were found among 29 samples in the current study.…”
Section: Discussioncontrasting
confidence: 37%
“…Thus, a mistaken diagnosis could be made if only the NAT was performed as a supplemental test for the screening test [Busch et al, 2006; Zhang et al, 2007]. HCV RNA is not detectable during the transition between acute and chronic phases of hepatitis C infection [Williams et al, 2002] because the anti‐HCV titer increases during infection and the HCV RNA load declines [Busch et al, 2000; Cavazza and Lagging, 2005]. In addition, intermittent HCV RNA positivity has been observed in patients with chronic HCV infection [Alter et al, 1992; Thomas et al, 2000; Larghi et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Indeterminate reactivity against the NS5 antigen has been shown to be associated with HCV viremia in clinical samples from patients, but not in blood donors. 16 In newer anti-HCV tests the NS5 antigen has been excluded to improve test specificity.…”
Section: Discussionmentioning
confidence: 99%